PROFIL HASIL BELAJAR EKSPERIMEN RANGKAIAN RESISTOR MAHASISWA POLITEKNIK - I Gede Rasagama (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
The study aim is to determine the profile of learning outcomes of resistor circuits experiment (RCE), before and after reconditioning learning facilities (job-sheet). Component of learning outcomes of type I includes the ability to accomplish a task preliminary, observational data and calculations, questions answer, sources of error, conclusions, and a bibliography, before and after reconditioning job-sheet. Component of learning outcomes of type II includes increased understanding of resistor circuits concepts (N-Gain) and their retention. The concept includes the experiment goals, KCL, KVL, Ohm's Law, and the nature of circuits. The subjects were students of Class I Prodi Energy Conservation D-IV POLBAN. The research activities carried out consist of in five phases: preparation, data collecting, data processing and analysing, discussion and formulation of conclusions. The research result shows RCE before reconditioning job-sheets that gave the highest learning outcomes type I on observational data and calculations, followed by preliminary tasks, questions answer, a bibliography, conclusions, and the lowest was the source of error. After reconditioning job-sheet, the highest of learning outcomes type I happened at observational data and calculations, followed by preliminary tasks, question answers, sources of error, a bibliography, and the lowest is the conclusion. The overall learning outcomes of type I, after reconditioning job-sheet, is better than before reconditioning job-sheet, with N-Gain is 12%. N-Gain of learning outcomes of type II before reconditioning job-sheet, is the highest on Ohm's Law, the nature of circuit, KVL, KCL, and the lowest is on experimental purposes. N-Gain of learning outcomes of type II after reconditioning job-sheet, is the highest on the nature of circuit, the experiment purpose, Ohm's Law, KCL and the lowest is on the KVL. The overall N-Gain of learning outcomes of type II, before reconditioning job-sheet of 27% and after reconditioning job-sheet of 25%. Retention of learning outcomes of type I has the same pattern as type II, both before and after reconditioning job-sheet, which is likely to increase. Keywords: Profile of learning outcomes, resistor circuits experiment, polytechnic students.